Influence of Critical Zone Architecture and Snowpack on Streamflow Generation Processes: A Mountain‐Meadow Headwater System in a Mediterranean Climate - P. Z. Klos; R. G. Lucas; M. H. Conklin (Water Resources Research)
Abstract Observations from a granitic watershed within a Mediterranean climate reveal the hydrologic and critical zone functioning of a perennial stream headwater and its upslope contributing area within a meadow system in the Sierra Nevada, California. Chemical analysis (diagnostic tools of mixing models, end member mixing analysis, tritium, etc.) and physical data (stream stage, piezometers, soil water, snowpack, etc.) indicate there are two primary pathways of water input into a headwater stream sourced from a mountain meadow. One input is a shallower and younger subsurface pathway with water that resembles snowpack chemistry, and the other a deeper and older subsurface pathway with water that reflects the chemistry of the groundwater derived from the contributing hillslopes. Multi‐year observations reveal that regardless of snowpack amount, during the period of peak hillslope infiltration, shallow and deep pathways in the hillslope behave similarly to initiate headwater streams. However, during summer dry periods, similarities in active pathways within the meadow center are not maintained between high and low snowpack years. With less snow, perennial groundwater discharge within the meadow center is eliminated, becoming only a seasonal source at the meadow's outlet. At the meadow's edge, geophysically observed downslope thinning in saprolite thickness creates reduced lateral transmissivity and initiation points for headwater streams via enhanced groundwater discharge of upslope water. Combined, these findings suggest how loss of snowpack and critical zone structure can together mediate hydrologic function in a wet meadow system in a Mediterranean climate. Creating new understanding about the stability of hydraulic functioning in headwater wet‐meadow systems under a changing climate.